بدائل العقوبات السالبة للحرية في التشريع الجزائري - أمحمدي بوزينة, آمنة (revue mofakir, 2018)
Proven practical experience of the futility of negative punishment of freedom to achieve deterrence, rehabilitation and reform, on the grounds that the latter is characterized by cruelty and deprivation of liberty of the individual; the statistics indicate that the lute crimes continues to increase, and that the prison has become unbearable accommodate the huge number and the steady criminals, has It focused on punitive politics of contemporary search for punitive   alternatives to replace them, and considered the death to work for the public benefit at the moment of the most important of these alternatives, where  successive legislation comparison introduced as a means of reform and rehabilitation of sentenced persons and re-integration into society, and I have followed the Algerian legislature the example of other legislation that adopted This penalty and took in the year 2009 alternative punishment to imprisonment in force operative and which does not exceed the year, we have tried through this study to shed light on all matters relating to the death penalty and what distinguishes it by highlighting the positive role of the death work public utility as an alternative for negative punishment short of freedom period.